Upaya Meningkatkan Minat dan Hasil Belajar IPS menggunakan Metode Teka-Teki Silang di Kelas VIII 3 Upt Smp Negeri 1 Alla Kabupaten Enrekang - Ratna Jita (Jurnal Syntax Transformation, 2022)
This research was carried out in class VIII 3 UPT SMP Negeri 1 Alla, Enrekang Regency by applying the Crossword Puzzle learning method to determine the increase in student interest and learning outcomes. This research is a classroom action research (Classroom Action Research). The subjects of this study were 26 students of class VIII-3 UPT SMP Negeri 1 Alla. This research took place in 3 cycles. Each cycle consists of one meeting. Data collection techniques using observation, field notes, and documentation. The types of data collected are observational data on interest in learning and data on group learning outcomes. The data analysis technique used is qualitative data analysis technique which consists of data reduction, data presentation and conclusion drawing. For the validity of the data used triangulation. The results of the study can be concluded as follows: 1) The application of the Crossword Puzzle learning method can increase students' interest in learning social studies in class VIII-3 UPT SMP Negeri 1 Alla. This is evidenced by an increase in the average percentage of indicators of student interest in learning each cycle. In the first cycle the average percentage of students' interest in learning indicators is 62%. In the second cycle to 70% or an increase of 8%. In the third cycle, it increased by 18% to 88%. 2) The application of the Crossword Puzzle learning method can improve student learning outcomes. This is evidenced by the percentage of students who achieved the KKM score in the first cycle of 20% increased to 60% in the second cycle. Furthermore, it still increased to 80% in cycle III.